Sistem Pengurusan Maklumat Ko-kurikulum SK To’ Uban - Zanalabidin, Nur Ain Shahira; Ab. Aziz, Ruhaya (Applied Information Technology And Computer Science, 2021)
Co-curriculum Information Management System SK To 'Uban is a web-based system developed to assist SK to' Uban in managing the school's co-curriculum information. The use of manual systems that are still used by SK To 'Uban is a major problem that makes work on school co-curriculum information to be slow and less effective. This causes the process of updating the co-curriculum data to slow and face data loss problems. In addition, the documentation process of school information is also slow and irregular. Therefore, this web-based system is developed to address the problem. The software development model used for this project is a prototype model that involves five important phases of planning phase, analytical phase, design phase, implementation phase and testing phase. This model is very suitable and flexible for use in this project. This system is developed web-based built using PHP programming language and MySQL as a database. The system provides several major modules namely login modules, admin modules, teacher modules, activity modules, co-curriculum modules, allocation application modules and report modules. In conclusion, this developed SK To 'Uban Co-curriculum Information Management System is expected to assist SK to' Uban school to improve the effectiveness of the co-curriculum management process which is better than the previous system of the manual system.